Regional Pollination Activity by Moth Migration in Athetis lepigone - Huiru Jia; Yuchao Chen; Xiaokang Li; Yunfei Pan; Dazhong Liu; Yongqiang Liu; Kongming Wu (Plants, 2023)
Nocturnal moths (Lepidoptera) are important pollinators of a wide range of plant species. Understanding the foraging preferences of these insects is essential for their scientific management. However, this information is lacking for most moth species. The present study was therefore conducted to delineate the host plant feeding and pollination ranges of an agriculturally important nocturnal moth species Athetis lepigone by identifying the pollen species adhering to their bodies during long-distance migration. Pollen grains were dislodged from 1871 A. lepigone migrants captured on Beihuang Island in the Bohai Strait between 2020 and 2021. This region is a key seasonal migration pathway for A. lepigone in northern China. Almost 20% of all moths sampled harbored pollens, providing direct evidences that this moth species may serve as pollinators. Moreover, at least 39 pollen taxa spanning 21 plant families and 31 genera were identified, with a preference for Asteraceae, Amaranthaceae, and Pinaceae. Additionally, the pollen adherence ratios and taxa varied with moth sex, inter-annual changes, and seasonal fluctuations. Most importantly, the pollen taxa were correlated with insect migration stages and indicated that A. lepigone bidirectionally migrates between central China (Shandong, Hebei, and Henan Provinces) and northeastern China (Liaoning Province). Overall, the findings of the present work provide valuable information on the pollination behavior, geographical origins, and pollination regions of A. lepigone moths and could facilitate the design and optimization of efficacious local and regional management strategies for this important insect.